2015
DOI: 10.3109/10520295.2015.1063005
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid treatment of acetaminophen-induced rat liver damage

Abstract: Acetaminophen (paracetamol) is a well-tolerated analgesic and antipyretic drug when used at therapeutic doses. Overdoses, however, cause oxidative stress, which leads to acute liver failure. Alpha lipoic acid is an antioxidant that has proven effective for ameliorating many pathological conditions caused by oxidative stress. We evaluated the effect of alpha lipoic acid on the histological and histochemical alterations of liver caused by an acute overdose of acetaminophen in rats. Livers of acetaminophen-intoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In line with this finding, Galal et al, [16], Alipour et al, [28], Lee et al, [29], Mahmoud et al, [30] and Bektur et al, [31] previously reported that APAP caused marked liver damage as noted by significantly increased activities of serum AST and ALT. Moreover, Hu et al, [32] found high APAP dose caused ALT release, necrosis, irreversible mitochondrial dysfunction, and hepato-cellular death.…”
Section: Discussionsupporting
confidence: 56%
“…In line with this finding, Galal et al, [16], Alipour et al, [28], Lee et al, [29], Mahmoud et al, [30] and Bektur et al, [31] previously reported that APAP caused marked liver damage as noted by significantly increased activities of serum AST and ALT. Moreover, Hu et al, [32] found high APAP dose caused ALT release, necrosis, irreversible mitochondrial dysfunction, and hepato-cellular death.…”
Section: Discussionsupporting
confidence: 56%
“…This is in line with the previous data showing that the use of antioxidants such as alpha lipoic acid does not protect the liver fully from APAP-induced acute toxicity. 45 …”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that ALA possesses potent biological antioxidant activities, scavenging reactive oxygen species and reactive nitrogen species as well as chelating redox-active metals (e.g., iron and copper). Due to these properties of ALA, Mahmoud et al [70] investigated the role of ALA in the treatment of acetaminophen-induced liver damage in rats. 18 rats were randomly subdivided in 3 groups: a control group, which were given 1 ml of 50% propylene glycol in water orally, an acetaminophen (APAP) group receiving 3 g/kg APA in 50% propylene glycol administered orally (acute overdose), and an ALA + APAP group receiving a single 100 mg/kg dose of ALA in 0.5% alkaline saline (0.5% NaOH) orally followed by an overdose of APAP (3 g/kg) 1 h after ALA administration.…”
Section: Possible Therapeutic Effects Of Antioxidants: From Bench mentioning
confidence: 99%